Climate-Smart Agriculture investment portfolios for the Southern Plains in Jamaica - Eitzinger, Anton; Campbell, Donovan; Lizarazo, Miguel; Tomlinson, Jhannel; Navarrete-Frias, Carolina (2022)
The Southern Plains are Jamaica’s breadbasket, but they are highly exposed to drought and heat, irregular rainfalls, and hurricanes. This Policy Brief presents the main findings and policy recommendations of the project 'Capacity Building Program to Improve Stakeholder Resilience and Adaptation to Climate Change in Jamaica (CBCA).